Analisis Potensi Unggulan dan Daya Saing Komoditas Tanaman Perkebunan di Kabupaten Jembrana - NI MADE MEIDAYANI; MADE ANTARA; WIDHIANTHINI WIDHIANTHINI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2021)
Analysis of Superior Potential and Competitiveness of Plantation Crop Commodities in Jembrana Regency Plantation has a strategic position in the development of the agricultural sector in Jembrana. The research objective is to identify the leading plantation crop commodities in Jembrana Regency and to identify the competitiveness of the plantation crop commodities in each District in Jembrana Regency. Data were analyzed using Location Quetient (LQ), Dynamic Location Quotient (DLQ), and Shift Share Analysis (SSA) methods. The results show that each District in Jembrana Regency has different superior and number of plantation crops commodities that analyzed from the 11 plantation crops commodities, but these superior plantation crops commodities did not necessarily have competitiveness. The superior plantation crop commodities based on the results of the LQ analysis include deep coconut, deres coconut, hybrid coconut, clove, nutmeg, cocoa, robusta coffee, vanilla, coconut, kapok and tobacco. Plantation commodities in each district in Jembrana Regency that have the competitiveness are: deep coconut, deres coconut, early coconut and vanilla (Melaya District), deres coconut, hybrid coconut, early coconut, cocoa, robusta coffee, vanilla and nutmeg (Negara District), hybrid coconut, cocoa and nutmeg (Jembrana District), deep coconut, hybrid coconut, clove, robusta coffee and nutmeg (Mendoyo District), Pekutatan District does not have competitive plantation crops commodities.